PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR IPS SISWA KELAS VIII MTs NURUL INSAN LENGGADAI HULU, KEC.RIMBA MELINTANG, KAB. ROKAN HILIR - Leni Leni; Gimin Gimin; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine the effect of the number head together (NHT) type of cooperative learning model on students INTEGRATED IPS learning outcomes IN CLASS VIII. This research was conducted at MTs Nurul Insan in the academic year 2018/2019. This research is experimental research. The population in class VIII consisted of 90 students from 3 classes while the study sample consisted of 60 students. For the experimental class totaling 30 students and for the control class totaling 30 students. For sampling classes using random sampling. The research instruments used are observation sheets (teacher activities, student activities and documentation) and data collection tools (pretest and posttest). The analysis of INTEGRATED IPS learning outcomes data using different test shows that the INTEGRATED IPS learning outcomes use NHT with an average value of 72.63, is greater than the class using the lecture method with an average value of 65.4. The difference is close to significance. Based on the results of the N-Gain score obtained a value of 0.36 which lies at a score of 0.7> gain> 0.3. So, it can be concluded that the NHT type of cooperative learning model towards the learning outcomes of experimental class students is in the moderate category and deserves to be considered as one of the learning models used in the learning process.Key Words: Model Number Head Together (NHT), Learning Outcomes